Combined use of stent angioplasty and mechanical thrombectomy for acute tandem internal carotid and middle cerebral artery occlusion - Gao, Feng (Neuroradiol J, 2015)
PURPOSE: Tandem internal carotid and middle cerebral artery occlusion carries a grave prognosis, with intravenous and intra-arterial thrombolytics having low efficacy. Currently, endovascular therapy is a promising means for treatment in which the proximal carotid lesion can be treated with angioplasty and stenting, whilst mechanical thrombectomy can be used for the treatment of the distal occlusion. Two approaches can be used – the antegrade (proximal-to-distal) approach or the retrograde (distal-to-proximal) approach, although there has not yet been any consensus on which is the better approach. CASE REPORT: We present two patients with tandem occlusions, one treated using the antegrade and one using the retrograde approach, with different revascularization outcomes, despite having similar functional outcome on follow-up. CONCLUSION: The combined use of stent angioplasty and mechanical thrombectomy can be used to treat tandem occlusions, and with procedural modifications, the antegrade approach may more easily achieve technical success.